SYSTEMATIC REVIEW OF MYOPIC CHOROIDAL NEOVASCULARIZATION MANAGEMENT AND LONG-TERM OUTCOMES - Leonardo Joaquim Silva Monteiro (2021)
Purpose: To summarize the current understanding of myopic choroidal neovascularization (mCNV) and to review the latest data regarding predictive factors of long-term morphological and visual outcomes in patients with mCNV treated with intravitreal anti-vascular endothelial growth factor (anti-VEGF) drugs. Clinical relevance: Pathological myopia (PM) is one of the main causes of low vision worldwide. It is estimated around 3% of the world population suffers from PM. Of the affected individuals, 5-11% will develop mCNV. Furthermore, 35% of the patients with mCNV will develop bilateral disease in an 8-year period. Numerous studies demonstrated the short-term efficacy of anti-VEGF therapies in mCNV, establishing them as first line treatment. Nevertheless, until recently, few studies provided long-term data on the safety and efficacy of these therapies in patients with mCNV. Methods: We conducted a literature review in September 2020 of all English-language articles in PubMed resulting from searches of the following terms: "choroidal neovascularization" (MESH) AND "myopia" (MESH) OR "Myopia, degenerative" (MESH) OR "myopic macular degeneration" OR "myopic maculopathy" OR "myopic retinopathy" OR "pathological myopia" OR "pathologic myopia". Results: We screened a total of 431 abstracts. 62 articles were deemed relevant for full publication review. We excluded a further 18, but 29 additional articles were identified through reference lists search. This resulted in 73 articles being used to develop this review. Conclusions: Available long-term data for anti-VEGF agents are encouraging and significant gains in best corrected visual acuity (BCVA) have been observed at up to seven years of follow-up. Notwithstanding, many patients experience stabilization or a decrease in their BCVA over time due to development or progression of perilesional chorioretinal atrophy (CRA). In fact, anti-VEGF treatment does not prevent development of new or enlarged areas of CRA around the regressed CNV lesion (perilesional CRA). Future studies are required to identify therapies that prevent perilesional CRA development/progression.